PLASTY WITH INTRAOPERATIVE BALLOON STRETCHING OF LOCAL TISSUES OF THE TRUNK AREA (Conferencea, 2022)
In the world practice at present, the development and improvement of the results of treatment of patients with post-burn cicatricial defects of the body continue to be the most relevant.